CHILDHOOD NEGLECT AND OBSESSION: A PSYCHOANALYTIC LENS ON THE ROCKING HORSE WINNER BY D.H LAWRENCE - Ali, Muhammad Ilham (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2025)
The short story "The Rocking-Horse Winner" by D.H. Lawrence offers a profound exploration of human psychology, focusing on desire, obsession, and the consequences of unbridled ambition. This study employs a psychoanalytic approach to analyze the uncontrollable obsession of the main character, Paul, particularly through the lens of Freud's Oedipus Complex theory. This research aims to explore the underlying factors that drive Paul’s obsession with luck and money in D.H. Lawrence’s “The Rocking-Horse Winner,” with a particular focus on the psychological and emotional influences stemming from his relationship with his mother. It also seeks to examine how these motivations shape the narrative and contribute to the story’s broader themes of materialism, identity, and emotional neglect. This article also highlights the potent symbolism within the story, including the rocking horse and the house of whispers, which symbolize Paul's inner turmoil and the tragic outcomes of his obsession. Comparative analysis with Jung’s and Lacan’s theories further enriches the understanding of Paul's psychological complexity, providing insights into how his obsession influenced his mental state and family relationships. The findings contribute to a deeper understanding of the story's psychological and symbolic dimensions, offering valuable insights into the impact of parental influence on a child's mental health and behavior.